Silicon-based negative electrode material and preparation method and application thereof

The silicon-based negative electrode material with an egg yolk shell structure was prepared by alkaline etching, which solved the problem of poor electrochemical performance caused by the damage to the SiOC negative electrode material structure, and achieved high cycling stability and excellent electrochemical performance.

CN119797363AActive Publication Date: 2025-04-11SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411997469.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing silicon oxide carbon (SiOC) negative electrode materials have problems such as low inherent electron conductivity, low ionic conductivity, and large volume expansion, which leads to problems such as pulverization of the electrode material, loss of electrical contact with the current collector, and excessive SEI growth, which hinders its commercialization.

Method used

The silicon-based negative electrode material with an egg yolk shell structure was prepared by alkaline etching method. The mesoporous silicon spheres were etched through a weak alkaline solution to selectively remove the inorganic silicon dioxide components in the hybrid silica spheres to obtain a unique egg yolk shell structure, which effectively alleviates the structural expansion of the silicon-based negative electrode material.

Benefits of technology

The method is simple, has high repeatability and gentle reaction, which better retains the structural integrity of the egg yolk shell structure and significantly improves the electrochemical performance of the silicon-based negative electrode material, including ultra-long cycle stability, excellent charging specific capacity, Coulomb efficiency and capacity retention rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797363A_ABST
    Figure CN119797363A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-based negative electrode material and a preparation method and application thereof. The preparation method comprises the following steps: (1) adding an inorganic silicon source into a mixed solution A containing mesoporous silica and a template agent, and carrying out a sol-gelation reaction to prepare silica spheres; and (2) etching the silicon dioxide balls by using a weakly alkaline solution for 2-5 hours to prepare the silicon-based negative electrode material. The preparation method disclosed by the invention is simple, high in repeatability and mild in reaction; the prepared silicon-based negative electrode material well retains the structural integrity of the yolk shell structure, and further obtains excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-based negative electrode material and a preparation method and application thereof. Background Art

[0002] In recent years, the rapid development of electric vehicles has promoted the progress of lithium-ion batteries. The commercial negative electrode material graphite has been increasingly unable to meet people's needs for high energy density batteries due to its low capacity. Therefore, silicon-based materials have attracted the attention of researchers due to their ultra-high specific capacity and safe operating voltage. In recent years, silicon oxygen carbon (SiOC) negative electrodes have attracted widespread attention due to their high cycle stability, suitable potential platform, low cost and environmental friendliness. However, SiOC negative electrodes still have problems such as low inherent electronic conductivity, low ionic conductivity, and large volume expansion, which leads to a series of problems such as electrode material pulverization, loss of electrical contact with the current collector, and excessive growth of SEI. These problems have seriously hindered the commercialization of SiOC-based negative electrodes.

[0003] In the past few decades, researchers have proposed various methods to solve the problems associated with SiOC-based anodes. Common modification strategies include composite with carbon-based materials, nanostructure design, and surface modification. Carbon modification is considered to be an efficient method to solve the problems associated with SiOC-based anodes. Because it can significantly improve the conductivity of SiOC, optimize the electrochemical kinetics of SiOC materials, and partially alleviate the volume expansion of SiOC. However, SiOC will eventually cause the active materials to break and pulverize due to repeated expansion during long-term cycling. Nanostructure design can reduce the size of active materials or reserve a certain amount of void space for active materials, thereby alleviating the volume expansion and contraction of SiOC during lithiation and embrittlement. Unfortunately, nanostructured active materials usually have a large specific surface area, resulting in extensive contact between active materials and electrolytes, leading to excessive SEI growth and reduced ICE. Surface modification to form a core-shell or yolk-shell structure can effectively reduce the interfacial contact between the electrode and the electrolyte, thereby minimizing side reactions.

[0004] The yolk-shell structure has received extensive attention in many scientific research fields due to its unique structural advantages. In the study of silicon-based negative electrodes for lithium-ion batteries, the huge volume expansion of silicon during the charge and discharge process leads to particle crushing and the formation of an irregular SEI film. The cavity inside the yolk-shell structure can provide space for the volume expansion of silicon, thereby improving the structural stability. The traditional preparation process of the yolk-shell structure often uses strong acid or strong base etching to obtain the cavity, which will greatly damage the structure and thus reduce product performance. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the defect that the structure of the silicon-based material with yolk-shell structure in the prior art is destroyed, resulting in poor electrochemical performance, and provide a silicon-based negative electrode material and its preparation method and application. The present invention adopts an alkaline etching method to prepare a silicon-based negative electrode material with a yolk-shell structure. The preparation method is simple, highly repeatable and mild in reaction. The silicon-based negative electrode material prepared by the present invention better retains the structural integrity of the yolk-shell structure, and further obtains excellent electrochemical performance.

[0006] The present invention solves the above technical problems through the following technical solutions.

[0007] The inventors of the present application creatively used a mild weak alkaline solution to etch the mesoporous organosilicon spheres, selectively removing the inorganic silica components in the hybrid silica spheres to obtain a unique yolk-shell structure that can better preserve the integrity of the structure and effectively alleviate the structural expansion of the silicon-based negative electrode material, thereby obtaining ultra-long cycle stability.

[0008] The present invention provides a method for preparing a silicon-based negative electrode material, which comprises the following steps:

[0009] (1) adding an inorganic silicon source to a mixed solution A including mesoporous silica and a template agent to perform a sol-gel reaction to obtain silica spheres;

[0010] (2) A weakly alkaline solution is used to etch the silicon dioxide spheres, wherein the etching time is 2-5 hours to obtain a silicon-based negative electrode material.

[0011] In step (1), the silicon source used in the mesoporous silica may be an organic silicon source.

[0012] Among them, the organic silicon source can be selected from one or more of 1,4-bis(triethoxysilyl)benzene (BTEB), 3-methacryloxypropyltrimethoxysilane (MPTMOS), 3-mercaptopropyltrimethoxysilane (MPTMS), vinyltriethoxysilane (VTES), 3-aminopropyltriethoxysilane (APTES), phenyltrimethoxysilane (PTMS) and vinyltrimethoxysilane (VTMS), for example, one or more of 1,4-bis(triethoxysilyl)benzene (BTEB) and vinyltriethoxysilane (VTES).

[0013] In step (1), the mesoporous silica can be prepared by a sol-gel method. Preferably, the mesoporous silica is prepared by the following method: adding an organic silicon source to a mixed solution B including a template, a cosolvent, a solvent and an alkaline catalyst, and performing a sol-gel reaction to prepare the mesoporous silica.

[0014] Wherein, in the mixed solution B, the template can be selected from dodecyltrimethylammonium bromide (DTAB), tetradecyltrimethylammonium bromide (TTAB), hexadecyltrimethylammonium bromide (CTAB), octadecyltrimethylammonium bromide (OTAB), dodecyltrimethylammonium chloride (DTAC), tetradecyltrimethylammonium chloride (TTAC), hexadecyltrimethylammonium chloride (CTAC) or octadecyltrimethylammonium chloride (STAC), such as hexadecyltrimethylammonium bromide (CTAB).

[0015] Wherein, in the mixed solution B, the mass volume ratio of the template and the organosilicon source may be (100-3000) mg:1 mL, preferably (300-1000) mg:1 mL, for example 800 mg:1 mL.

[0016] Wherein, in the mixed solution B, the co-solvent can be selected from one or more of methanol, ethanol, ethylene glycol and isopropanol, such as ethanol.

[0017] Wherein, in the mixed solution B, the volume ratio of the organic silicon source to the co-solvent may be 1:(20-400), preferably 1:(100-200), for example 1:120.

[0018] Wherein, in the mixed solution B, the alkaline catalyst can be selected from one or more of ammonia water, triethanolamine, triethylamine, and diethylamine, such as ammonia water. The concentration of the ammonia water is preferably 10-30%, such as 25%.

[0019] Wherein, in the mixed solution B, the volume ratio of the organosilicon source to the alkaline catalyst may be 1:(1-40), preferably 1:(1-20), for example 1:4.

[0020] Wherein, in the mixed solution B, the solvent may be deionized water.

[0021] Wherein, in the mixed solution B, the volume ratio of the organosilicon source to the solvent may be 1:(50-1000), preferably 1:(100-400), for example 1:280.

[0022] Wherein, in the mixed solution B, the temperature of the sol-gel reaction may be 20-40°C, for example, 35°C.

[0023] Wherein, in the mixed solution B, the sol-gel reaction time may be 5-24 h, such as 6 h or 12 h.

[0024] In step (1), in the mixed solution A, the template agent can be selected from dodecyltrimethylammonium bromide (DTAB), tetradecyltrimethylammonium bromide (TTAB), hexadecyltrimethylammonium bromide (CTAB), octadecyltrimethylammonium bromide (OTAB), dodecyltrimethylammonium chloride (DTAC), tetradecyltrimethylammonium chloride (TTAC), hexadecyltrimethylammonium chloride (CTAC) or octadecyltrimethylammonium chloride (STAC), for example, hexadecyltrimethylammonium bromide (CTAB).

[0025] In step (1), in the mixed solution A, the mass ratio of the mesoporous silica to the template may be 1:(0.01-1), preferably 1:(0.01-0.5), for example 1:0.04.

[0026] In step (1), the mixed solution A may further include one or more of a co-solvent, a solvent and an alkaline catalyst.

[0027] Wherein, in the mixed solution A, the co-solvent can be selected from one or more of methanol, ethanol, ethylene glycol and isopropanol, such as ethanol.

[0028] Wherein, in the mixed solution A, the mass volume ratio of the mesoporous silica to the co-solvent may be 1 g:(4-10) mL, for example, 1 g:6 mL.

[0029] Wherein, in the mixed solution A, the alkaline catalyst can be selected from one or more of ammonia water, triethanolamine, triethylamine, and diethylamine, such as ammonia water. The concentration of the ammonia water is preferably 10-30%, such as 25%;

[0030] Wherein, in the mixed solution A, the mass volume ratio of the mesoporous silica to the alkaline catalyst may be 1 g:(0.1-1) mL, preferably 1 g:(0.1-0.5) mL, for example 1 g:0.2 mL.

[0031] Wherein, in the mixed solution A, the solvent may be deionized water.

[0032] Wherein, in the mixed solution A, the mass volume ratio of the mesoporous silica to the solvent may be 1 g:(10-20) mL, for example, 1 g:14 mL.

[0033] In step (1), the inorganic silicon source can be selected from tetraethoxysilane TEOS or vinyltriethoxysilane VTOS.

[0034] In step (1), in the mixed solution A, the mass volume ratio of the mesoporous silica to the inorganic silicon source may be 1 g:(0.01-1) mL, preferably 1 g:(0.1-0.5) mL, for example 1 g:0.05 mL.

[0035] In step (1), in the mixed solution A, the temperature of the sol-gel reaction can be 20-40°C, for example 35°C.

[0036] In step (1), in the mixed solution A, the sol-gel reaction time may be 10-24 hours, for example 12 hours.

[0037] In step (2), the solute of the weak alkaline solution can be selected from one or more of sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate and ammonia water, such as sodium carbonate or sodium bicarbonate.

[0038] In step (2), the solvent of the weak alkaline solution may be deionized water.

[0039] In step (2), the concentration of the weak alkaline solution may be 1-5 mol / L, for example 2.4 mol / L.

[0040] In step (2), the etching temperature may be 20-50° C., for example, 35° C. Within the applicable range, as the temperature increases, the etching effect is improved.

[0041] In step (2), the etching time is preferably 2-4 hours, for example 3 hours.

[0042] In the present invention, the size of the cavity inside the yolk-shell structure can be adjusted by controlling the parameter conditions of the etching process. Within the appropriate etching temperature and time range, the product structure can be effectively prevented from being destroyed or the etching being incomplete.

[0043] In step (2), the etching may be followed by a carbon coating operation. After the carbon coating, the carbon source is carbonized to form amorphous carbon, which plays a role in supporting and protecting and improving the conductivity of the material.

[0044] The carbon coating may include the following steps: reacting a mixed solution C including the etched product, resorcinol and formaldehyde, drying and calcining to obtain a silicon-based negative electrode material.

[0045] In the mixed solution C, the mass ratio of the etched product to the resorcinol may be 1:(0.2-0.8), for example, 1:0.47.

[0046] In the mixed solution C, the mass volume ratio of the resorcinol to the formaldehyde may be (600-800) mg:1 mL, for example, 700 mg:1 mL.

[0047] The mixed solution C may further include a surfactant and / or a co-solvent.

[0048] The surfactant may be selected from dodecyltrimethylammonium bromide (DTAB), tetradecyltrimethylammonium bromide (TTAB), hexadecyltrimethylammonium bromide (CTAB), octadecyltrimethylammonium bromide (OTAB), dodecyltrimethylammonium chloride (DTAC), tetradecyltrimethylammonium chloride (TTAC), hexadecyltrimethylammonium chloride (CTAC) or octadecyltrimethylammonium chloride (STAC), for example hexadecyltrimethylammonium bromide (CTAB).

[0049] In the mixed solution C, the mass ratio of the etched product to the surfactant may be 1:(0.2-0.8), for example, 1:0.53.

[0050] The co-solvent may be selected from one or more of methanol, ethanol, ethylene glycol and isopropanol, such as ethanol.

[0051] In the mixed solution C, the mass volume ratio of the etched product to the co-solvent may be 1 mg:(150-200) mL, for example, 1 mg:186.7 mL.

[0052] The reaction temperature may be 20-40°C, such as 35°C.

[0053] The reaction time may be 20-30 hours, for example 24 hours.

[0054] The calcination temperature may be 600-1000°C, for example 800°C.

[0055] The calcination time may be 2-4 hours, for example 3 hours.

[0056] The present invention also provides a silicon-based negative electrode material, which is prepared by the above preparation method.

[0057] In the present invention, the porosity of the silicon-based negative electrode material may be greater than 50%.

[0058] In the present invention, the average pore size of the silicon-based negative electrode material may be 5-10 nm.

[0059] The present invention provides a silicon-based negative electrode material. The silicon-based negative electrode material is an egg yolk shell structure, comprising a core, an outer shell, and a cavity between the core and the outer shell; the core and the outer shell are both SiOC.

[0060] In the present invention, preferably, the outer side of the shell further includes a carbon layer.

[0061] In the present invention, the porosity of the silicon-based negative electrode material may be greater than 50%.

[0062] In the present invention, the average pore size of the silicon-based negative electrode material may be 5-10 nm.

[0063] The present invention also provides application of the silicon-based negative electrode material in lithium-ion batteries.

[0064] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0065] The reagents and raw materials used in the present invention are commercially available.

[0066] The positive and progressive effects of the present invention are:

[0067] The present invention adopts an alkaline etching method to prepare a silicon-based negative electrode material with an egg yolk-shell structure. The preparation method is simple, highly repeatable and mild in reaction. The silicon-based negative electrode material prepared by the present invention better retains the structural integrity of the egg yolk-shell structure; and further obtains excellent electrochemical properties, such as charge specific capacity, coulomb efficiency and capacity retention rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 Schematic diagram of the synthesis of silicon-based negative electrode materials in Example 1.

[0069] Figure 2 This is the SEM image of the silicon-based negative electrode material prepared in Example 1.

[0070] Figure 3 This is the TEM image of the silicon-based negative electrode material prepared in Example 1.

[0071] Figure 4 The structure characterization diagram of the silicon-based negative electrode material prepared in Example 1; wherein, Figure 4 Part a in the figure is the X-ray diffraction pattern. Figure 4 Part b in the figure is the Fourier transform infrared spectrum. Figure 4 Part c in the figure is the Raman spectrum. Figure 4 Part d in the figure is the thermogravimetric analysis diagram. Figure 4 Part e in the figure is the nitrogen adsorption and desorption isotherm diagram. Figure 4 The f part in the figure is the pore size distribution diagram.

[0072] Figure 5 This is a rate performance diagram of the silicon-based negative electrode material prepared in Example 1.

[0073] Figure 6 This is a long cycle performance diagram of the silicon-based negative electrode material prepared in Example 1. DETAILED DESCRIPTION

[0074] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product instructions.

[0075] Example 1

[0076] Synthesis of YS-PMOs: Add 70mL of deionized water, 30mL of anhydrous ethanol and 200mg of CTAB to a three-necked flask, stir at 35°C for 10min, and add 1mL of ammonia water (mass percentage is 25%). After reacting for 1h, drop 0.25mL of BTEB and react for 6h. Centrifuge and dry the solution after the reaction to obtain about 5g of mesoporous silica. Add 30mL of anhydrous ethanol, 70mL of deionized water and 200mg of CTAB again, stir for ten minutes, add 1mL of ammonia water (25%), stir at 35°C for 1h, and then add 0.25mL of TEOS. After reacting for 12h, centrifuge and dry to obtain a core-shell structure. Put the product into 30mL of Na2CO3 solution (2.4M), stir at 35°C for 3h, and centrifuge and dry to obtain yolk-shell structure YS-PMOs.

[0077] Synthesis of YS@C: Take 1.5g YS-PMOs, add 280mL deionized water, 120mL Water ethanol, 800 mg CTAB, after reacting for 10 min, add 4 mL ammonia water (25%), after reacting for 0.5 h, add 700 mg resorcinol, after reacting for 0.5 h, add 1 mL formaldehyde. After reacting at 35 ° C for 24 h, centrifuge and dry. In a H2 / Ar mixed atmosphere, calcine at 800 ° C for 3 h. YS@C is obtained.

[0078] Schematic diagram of the synthesis of silicon-based negative electrode materials Figure 1 shown.

[0079] Example 2

[0080] The only difference from Example 1 is that TEOS is replaced by VTOS.

[0081] Comparative Example 1

[0082] The only difference from Example 1 is that the sodium carbonate etching time is adjusted to 1 hour.

[0083] Comparative Example 2

[0084] The only difference from Example 1 is that the sodium carbonate etching time is adjusted to 6 hours.

[0085] Comparative Example 3

[0086] The only difference from Example 1 is that the sodium carbonate etching time is adjusted to 12 hours.

[0087] Effect Example 1 Morphology

[0088] The silicon-based negative electrode materials prepared in Example 1 and Comparative Examples 1-3 were subjected to morphology tests.

[0089] Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to observe the structural integrity. Figure 2 and Figure 3 They are SEM and TEM images of the silicon-based negative electrode material prepared in Example 1, respectively. It can be seen intuitively from the figures that the silicon-based negative electrode material prepared in the present invention has a complete structure, which presents an egg yolk shell structure, including a SiOC core, a cavity, a SiOC shell and a carbon layer, and the carbon layer is on the outside of the SiOC shell.

[0090] The silicon-based negative electrode material prepared in Comparative Example 1 is a solid sphere, which only has SiOC and carbon layers, and the interior is not etched and has no cavity.

[0091] The silicon-based negative electrode material prepared in Comparative Example 2 has a yolk-shell structure, including a SiOC core, a cavity, a SiOC shell and a carbon layer, but the pores are etched larger, the cavity volume is larger, and the core of the yolk part is smaller. It can be inferred that because the part providing capacity is etched too much, the prepared silicon-based negative electrode material also exhibits poor rate performance.

[0092] The silicon-based negative electrode material prepared in Comparative Example 3 is a hollow sphere, with only a SiOC shell and a carbon layer, and the internal organic silicon sphere is completely etched.

[0093] Effect Example 2 Physical and Chemical Properties

[0094] The physical and chemical properties of Example 1 were tested.

[0095] Depend on Figure 4 It can be seen that YS@C and its intermediate products in the synthesis process are all amorphous.

[0096] X-ray diffraction (XRD) analysis can provide crystal structure information, such as Figure 4 As shown in part a of the figure, all samples show the characteristics of amorphous diffraction peaks. A large broad peak appears at 20°-30°, representing the 002 peak of carbon. A weaker broad peak appears at 40-45°, representing the 100 peak of carbon.

[0097] Fourier transform infrared spectroscopy (FTIR) found that ( Figure 4 In YS@C and P@C, the characteristic peaks of organic substances in PMOs (3000 cm -1 and 1000cm -1 ) disappears, indicating that the hydrogen in the organic functional groups is removed during the high-temperature carbonization process.

[0098] The amorphous carbon in YS@C is at 1340 cm -1and 1600cm -1 There are two Raman peaks at Figure 4 As shown in part c of the graphite ... 2 Hybridization is conducive to the formation of graphitic carbon. YS@C loses more SiO2 produced by TEOS hydrolysis during the etching process, so the degree of graphitization is higher.

[0099] The carbon content of the samples was further measured by thermogravimetric method, such as Figure 4 As shown in part d of the figure, the carbon content of YS@C is 75.51%. The carbon in YS@C comes from two aspects: the phenolic resin and siloxane (styrene) coated on the outermost layer.

[0100] In addition, in order to explore the surface condition of YS@C, we conducted nitrogen adsorption and desorption tests (BET) on the samples. The specific surface area and porosity tests (BET) can reflect the stability of the structure. Figure 4 As shown in part e, the material belongs to the type IV curve, and the hysteresis loop is H4, indicating the existence of irregular slit mesopores and macropores.

[0101] The specific surface area of ​​YS@C is 17.041m 2 g -1 . The mesopores were analyzed according to the Barret-Joyner-Halenda model ( Figure 4 (part f in the figure), the average pore size of YS@C is 2.371.

[0102] Effect Example 3 Electrochemical Performance

[0103] The electrochemical performance of the silicon-based negative electrode material prepared in Example 1 was tested.

[0104] (1) Button battery preparation

[0105] According to the mass ratio of 94.5:1.5:1.5:1.5, silicon-based negative electrode material, conductive carbon black SP, sodium carboxymethyl cellulose CMC and styrene-butadiene rubber SBR were weighed respectively, stirred evenly in water to make negative electrode slurry, and evenly coated on copper foil using a coater to make a pole piece. The coated pole piece was placed in a vacuum drying oven at a temperature of 110°C and vacuum dried for 4 hours, and then pressed into a negative electrode; the simulated button cell was assembled in a German Braun glove box filled with argon, the electrolyte was 1M LiPF6+EC:EMC:DMC=1:1:1 (volume ratio), and the metal lithium sheet was the counter electrode.

[0106] (2) Electrochemical performance testing

[0107] Rate performance test: Take a button battery prepared as above, cycle it for five cycles at current densities of 0.1A / g, 0.2A / g, 0.5A / g, 1A / g and 2A / g, and then cycle it for five cycles at a current density of 0.1A / g, and detect the charge specific capacity, coulomb efficiency and capacity retention rate.

[0108] The test results of charge specific capacity are as follows: Figure 5 As shown, the black circle and gray circle represent the discharge capacity and charge capacity, respectively.

[0109] Long cycle performance test: Take two button batteries prepared as above, first cycle them for five cycles at a current density of 0.1A / g, then cycle them for 1000 cycles at current densities of 0.5A / g and 1A / g respectively, and detect the charge specific capacity, coulombic efficiency and capacity retention rate.

[0110] The test results of charge specific capacity and coulombic efficiency are as follows: Figure 6 shown.

[0111] The test result data is shown in Table 1 below.

[0112] Table 1

[0113]

[0114] It can be seen from the above table that with the increase of current density, the silicon-based negative electrode material prepared by the present invention can still maintain a relatively high charge specific capacity, coulombic efficiency and capacity retention rate, indicating that the silicon-based negative electrode material of the present invention has excellent rate performance.

[0115] In addition, when the current density reaches 0.5A g -1 and 1Ag -1 The silicon-based negative electrode material of the present invention can still maintain stable electrochemical performance during long cycles; after 1000 cycles, it can still maintain a high charge specific capacity, coulomb efficiency and capacity retention rate.

Claims

1. A method for preparing a silicon-based negative electrode material, characterized in that: It includes the following steps: (1) adding an inorganic silicon source to a mixed solution A including mesoporous silica and a template agent to perform a sol-gel reaction to obtain silica spheres; (2) The silicon dioxide spheres are etched with a weak alkaline solution for 2-5 hours to obtain a silicon-based negative electrode material.

2. The method for preparing a silicon-based negative electrode material according to claim 1, characterized in that: In step (1), in the mixed solution A, the template agent is selected from one or more of dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride and octadecyltrimethylammonium chloride, for example, hexadecyltrimethylammonium bromide; And / or, in step (1), in the mixed solution A, the mass ratio of the mesoporous silica to the template is 1:(0.01-1), preferably 1:(0.01-0.5); And / or, in step (1), the mixed solution A further comprises one or more of a co-solvent, a solvent and an alkaline catalyst; And / or, in step (1), the inorganic silicon source is selected from tetraethoxysilane or vinyltriethoxysilane; And / or, in step (1), in the mixed solution A, the mass volume ratio of the mesoporous silica to the inorganic silicon source is 1 g:(0.01-1) mL, preferably 1 g:(0.1-0.5) mL; And / or, in step (1), in the mixed solution A, the temperature of the sol-gel reaction is 20-40°C; And / or, in step (1), in the mixed solution A, the sol-gel reaction time is 10-24h.

3. The method for preparing a silicon-based negative electrode material according to claim 2, characterized in that: In the mixed solution A, the co-solvent is selected from one or more of methanol, ethanol, ethylene glycol and isopropanol, such as ethanol; And / or, in the mixed solution A, the mass volume ratio of the mesoporous silica to the co-solvent is 1 g:(4-10) mL; And / or, in the mixed solution A, the alkaline catalyst is selected from one or more of aqueous ammonia, triethanolamine, triethylamine, and diethylamine, such as aqueous ammonia; the concentration of the aqueous ammonia is preferably 10-30%, such as 25%; And / or, in the mixed solution A, the mass volume ratio of the mesoporous silica to the alkaline catalyst is 1 g:(0.1-1) mL, preferably 1 g:(0.1-0.5) mL; And / or, in the mixed solution A, the mass volume ratio of the mesoporous silica to the solvent is 1 g:(10-20) mL.

4. The method for preparing a silicon-based negative electrode material according to claim 1, characterized in that: In step (1), the silicon source used in the mesoporous silica is an organic silicon source; And / or, in step (1), the mesoporous silica is prepared by a sol-gel method; preferably, the mesoporous silica is prepared by the following method: an organic silicon source is added to a mixed solution B comprising a template, a cosolvent, a solvent and an alkaline catalyst, and a sol-gel reaction is performed to prepare the mesoporous silica.

5. The method for preparing a silicon-based negative electrode material according to claim 4, characterized in that: The organosilicon source is selected from one or more of 1,4-bis(triethoxysilyl)benzene, 3-methacryloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, vinyltriethoxysilane, 3-aminopropyltriethoxysilane, phenyltrimethoxysilane and vinyltrimethoxysilane, such as 1,4-bis(triethoxysilyl)benzene or vinyltriethoxysilane; and / or, in the mixed solution B, the template is selected from dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride or octadecyltrimethylammonium chloride, for example, hexadecyltrimethylammonium bromide; And / or, in the mixed solution B, the mass volume ratio of the template to the organosilicon source is (100-3000) mg:1 mL, preferably (300-1000) mg:1 mL; and / or, in the mixed solution B, the co-solvent is selected from one or more of methanol, ethanol, ethylene glycol and isopropanol, such as ethanol; And / or, in the mixed solution B, the volume ratio of the organosilicon source to the co-solvent is 1:(20-400), preferably 1:(100-200); And / or, in the mixed solution B, the alkaline catalyst is selected from one or more of ammonia water, triethanolamine, triethylamine, and diethylamine, such as ammonia water; the concentration of the ammonia water is preferably 10-30%, such as 25%; And / or, in the mixed solution B, the volume ratio of the organosilicon source to the alkaline catalyst is 1:(1-40), preferably 1:(1-20); And / or, in the mixed solution B, the volume ratio of the organic silicon source to the solvent is 1:(50-1000), preferably 1:(100-400); and / or, in the mixed solution B, the temperature of the sol-gel reaction is 20-40° C.; And / or, in the mixed solution B, the sol-gel reaction time is 5-24h.

6. The method for preparing a silicon-based negative electrode material according to claim 1, characterized in that: In step (2), the solute of the weak alkaline solution is selected from one or more of sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate and ammonia water, such as sodium carbonate or sodium bicarbonate; And / or, in step (2), the concentration of the weak alkaline solution is 1-5 mol / L, for example 2.4 mol / L; And / or, in step (2), the etching temperature is 20-50° C., for example, 35° C.; And / or, in step (2), the etching time is 2-4 hours, for example 3 hours; And / or, in step (2), the etching further includes a carbon coating operation; preferably, the carbon coating includes the following steps: reacting a mixed solution C including the etched product, resorcinol and formaldehyde, drying and calcining to obtain a silicon-based negative electrode material.

7. The method for preparing a silicon-based negative electrode material according to claim 6, characterized in that: In the mixed solution C, the mass ratio of the etched product to the resorcinol is 1:(0.2-0.8), for example, 1:0.47; And / or, in the mixed solution C, the mass volume ratio of the resorcinol to the formaldehyde is (600-800) mg:1 mL, for example, 700 mg:1 mL; And / or, the mixed solution C further comprises a surfactant and / or a cosolvent; Preferably, the surfactant is selected from dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride or octadecyltrimethylammonium chloride, such as hexadecyltrimethylammonium bromide; Preferably, in the mixed solution C, the mass ratio of the etched product to the surfactant is 1:(0.2-0.8), for example, 1:0.53; Preferably, the co-solvent is selected from one or more of methanol, ethanol, ethylene glycol and isopropanol, such as ethanol; Preferably, in the mixed solution C, the mass volume ratio of the etched product to the co-solvent is 1 mg:(150-200) mL, for example, 1 mg:186.7 mL; And / or, the reaction temperature is 20-40°C; And / or, the reaction time is 20-30h; And / or, the calcination temperature is 600-1000°C; And / or, the calcination time is 2-4h.

8. A silicon-based negative electrode material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 7; Preferably, the porosity of the silicon-based negative electrode material is greater than 50%; Preferably, the average pore size of the silicon-based negative electrode material is 5-10 nm.

9. A silicon-based negative electrode material, characterized in that: The silicon-based negative electrode material is an egg yolk shell structure, which includes a core, an outer shell, and a cavity between the core and the outer shell; the core and the outer shell are both SiOC; Preferably, the outer side of the shell further comprises a carbon layer; Preferably, the porosity of the silicon-based negative electrode material is greater than 50%; Preferably, the average pore size of the silicon-based negative electrode material is 5-10 nm.

10. Use of the silicon-based negative electrode material according to claim 8 or 9 in a lithium-ion battery.

Citation Information

Patent Citations

  • Preparation method of mesoporous silicon dioxide hollow sphere

    CN102167336A

  • Mesoporous-macropore composite hole structure silicon-aluminum oxide material and preparation method thereof

    CN108483473A

  • Graphitized carbon anode material and preparation method thereof

    CN110562950A

  • Method for in-situ preparation of porous silicon-carbon composite negative electrode material

    CN111646472A

  • Chlorella derived porous carbon / silicon composite material as well as preparation method and application thereof

    CN117317161A